PENGEMBANGAN PENDIDIKAN KEWIRAUSAHAAN PENGOLAHAN KEDELAI SEBAGAI SUMBER PANGAN DI SEKOLAH DASAR - Evy Marita Yuliwinarti; Ari Metalin Ika Puspita; Heru Subrata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Entrepreneurship is an attitude, soul and ability to create something new and has value and is useful for himself and others. Entrepreneurship education aims to form human beings as a whole (holistic), as humans who have character, understanding and skills as entrepreneurs. Entrepreneurship education needs to be instilled and developed from an early age through the role of parents and the world of education. Entrepreneurship education is very important for elementary school and Islamic elementary school children because it can shape the character of students in entrepreneurship so that in the future they are able to become successful Indonesian entrepreneurs. The purpose of this paper is to present the concept of entrepreneurship education in Elementary Schools and Madrasah Ibtidaiyah and its development and application in the surrounding environment. Where every student needs entrepreneurship education in order to create a useful work through learning activities.